Nilai Moral dalam Novel Sang Pemimpi karya Andrea Hirata: Kajian Nilai Pendidikan - Betaria Dwi Hastuti; Sri Wahono Saptomo; Sukarno Sukarno (Faculty of Languages and Arts, Universitas Negeri Padang, 2022)
Best-seller literary works in Indonesia are usually rich with life lessons and good moral values. This study aims to describe the moral values contained in the novel Sang Pemimpi by Andrea Hirata. This study used descriptive-qualitative method. This study uses data in the form of quotations from the dialogues of the characters that contain the value of moral education in the novel Sang Pemimpi by Andrea Hirata. The data collection technique used in the form of library technique as a basic technique, as well as reading and note-taking techniques as an advanced technique. The data analysis technique was carried out using dialectical techniques and content analysis techniques. The moral values in Andrea Hirata’s novel Sang Pemimpi include helpfulness, determination and commitment, cooperation, and humility.